Development of Ethnoscience-Based STEM-Based Electronic Learner Worksheets (E-LKPD) on Acid-Base Materials - Nabilah Ramadhani; Eddiyanto (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This research aims to develop an ethnoscience-integrated STEM-based Electronic Learner Worksheet (E-LKPD) on acid-base materials, as well as test its feasibility, practicality and effectiveness in improving student learning outcomes. The novelty of this research relies on the integration of local wisdom contexts into digital-based STEM syntax as a solution to bridge the understanding of chemical materials that tend to be abstract. The research method used is Research and Development (R&D) with a 4-D (Define, Design, Develop, Disseminate) model. The research subjects consisted of 3 expert validators (material and media), one chemistry teacher, and 20 students of class XI SCIENCE SMAS PAB 6 Helvetia as limited trial subjects. Effectiveness testing using a pretest-posttest One-Group experimental design. Data collection instruments in the form of validation sheets, practicality questionnaires, and learning outcome tests were analyzed using score percentage techniques and N-gain tests. The results of the study showed that the feasibility of E-LKPD from the material aspect obtained an average of 82.3% (very valid) and the media aspect obtained an average score of 85.8% (very valid). The level of practicality based on the teacher's response reached 98.4% (very practical). And the effectiveness test resulted in an increase in learning outcomes with an N-gain value of 70% or 0.70 (high category). The implications of this study show that ethnoscience-integrated STEM-based E-LKPD can be an alternative to innovative digital teaching materials that have the potential to support contextual and meaningful chemistry learning.